Pengaruh penerapan media robotik (robot line follower) terhadap kemampuan berpikir kreatif siswa - Dwi Aprilia Setia Asih; Indica Yona Okyranida; Deden Ibnu Aqil (UNIVERSITAS INDRAPRASTA PGRI, 2019)
This study aims to determine the effect of robotic media application (Robot Line Fillower) to the creative thinking ability of students. This research uses two groups to be studied that is group applied robotics (robot line follower) is called experiment class and control group or control class. sample determination using cluster random sampling technique. Data collection method used in this research is test method. The research instrument used is a matter of Posttest test of creative thinking ability. Data of students' creative thinking ability was tested using independent test samples T-Test. Based on data analysis, the result of significance (2-tailed) 0.000 below 0.05, then Ho is rejected, which means there is difference of creative thinking ability of control class and experiment class. The success of the experimental class on the creative thinking ability is caused by the impact of applying robotic line (robot line follower), in other words there is the effect of robot line fillower on the creative thinking ability of the students.